ANALISA STRATEGIS PADA INDUSTRI PENDUKUNG PARIWISATA DALAM MENCIPTAKAN BISNIS BERKELANJUTAN - Sulistyo, Agung; Arisanti, Yuli (Bajang Institute, 2025)
Business growth ultimately creates competitive competition and puts some businesses in a slump. This situation occurs due to the lack of strategies used. Many methods and concepts can be used to determine the competitive advantage of a business, one of which is through the analysis of the seven pillars of the Baldrige criteria. This criterion is one method that can be used to evaluate the performance of the strategy carried out. This study aims to analyze strategies carried out by MSME actors to create competitive advantages. This study uses a qualitative research design combined with a phenomenological approach. The objects of research in this study are MSME businesses that have achievements. Some of these MSME businesses include YAD Blangkon, AbaAli, Den Bagus, Modest-Art, Cilok Fatimah, Oliviaru, Boogie, Batik Thok Thil, Mahayeri, and Hokies Cakery. Data collection in this study used semi-structured interviews combined with the concept of the Baldrige criteria. The informants numbered 30 respondents consisting of business actors and consumers who use the product. Some stages of this method include transcription, reduction, categorization, and concluding. Triangulation techniques are used to maintain data quality. The study results indicate that MSME businesses fall into the Emerging Industry atau new business becomes a leader with a score of 641. These results were obtained based on the analysis of the Baldrige criteria instrument, including leadership patterns, strategic planning, focus on markets and customers, ability to analyze and manage knowledge, HR development, process standards, and business results obtained. This study can be a role model for other business actors to adopt in evaluating strategies to create business sustainability.